Sistem Dropshipping Mu’amalah Menurut Perspektif Ekonomi Islam - Alfrillianda, Aldian; Andriko (At-Tahdzib: Jurnal Studi Islam dan Muamalah, 2022)
Background. Human life today is not far from buying activities, both locally and domestically or internationally, humans practice trade in various ways and models that grow according to the conditions of the times. At first, buying and selling only met with sellers and buyers directly at the store with transaction facilities and products being traded. Aim. The research is intended to explain the muamalah dropshipping system from the point of view of Islamic economics. Methods. This research uses library research procedures or library research where the information obtained comes from authoritative sources, such as books and journals that are still relevant to the focus and review of the research. Results. The results of the research conclude that it is permissible for transactions that continue to grow in the economic process as long as they do not violate and do not conflict with Islamic principles, dropshipping transactions which have now become a citizen's routine can be carried out as long as the perpetrators understand. The transaction method, because the system is vulnerable and leads to the cancellation of the contract, is to sell objects that do not belong to him, and the development of technology greatly affects the growth of pressured fatwas issued. But on many sides, with the legal norms that have been summarized by previous scholars by looking at the equality of the illat law, a quick and appropriate legal answer can be found to determine the law in every legal event for which there are no clear legal requirements in the Qur'an and as - Sunnah.